Three-dimensional stress analysis for a thick plate of a composite material with a spatially locally curved structure - Tarim, ET; Akbarov, SD (SPRINGER, 2003)
The stress distribution in a thick rectangular plate of a multilayered composite with a spatially locally curved structure is investigated with the use of three-dimensional exact equations of elasticity theory. The investigations are carried out within the framework of the continuum approach proposed by Akbarov and Guz'. It is supposed that the plate edges are clamped and uniformly distributed normal forces are applied to its upper face. The corresponding boundary-value problem is solved by employing the three-dimensional FEM modeling. Numerical results for the normal stresses acting in the thickness direction of the plate are given. The influence of the spatial local curving on the distribution of these stresses is analyzed.
Keywords: composite; plate; spatial local curving; stress distribution; Mechanics; Materials Science; Polymer Science